Storage policies and maintenance support strategies in warehousing systems : doctoral thesis accepted by the University of Science and Technology of China, Hefei, People's Republic of China /: doctoral thesis accepted by the University of Science and Technology of China, Hefei, People's Republic of China. (2016) - Guo, Xiaolong
No abstract available